The potentiality of hydrocarbon generation of the Jurassic source rocks in Salam-3x well, - Mohamed M. El Nady; Fatma S. Ramadan; Emad A. Eysa; Nermin M. Said (Egyptian Journal of Petroleum)
The present work deals with the identification of the potential and generating capability of oil generation in the Jurassic source rocks in the Salam-3x well. This depending on the organo-geochemical analyses of cutting samples representative of Masajid, Khatatba and Ras Qattara formations, as well as, representative extract samples of the Khatatba and Ras Qattara formations. The geochemical analysis suggested the potential source intervals within the encountered rock units as follows: Masajid Formation bears mature source rocks and have poor to fair generating capability for generating gas (type III kerogen). Khatatba Formation bears mature source rock, and has poor to good generating capability for both oil and gas. Ras Qattara Formation constituting mature source rock has good to very good generating capability for both oil and gas. The burial history modeling shows that the Masajid Formation lies within oil and gas windows; Khatatba and Ras Qattara formations lie within the gas window. From the biomarker characteristics of source rocks it appears that the extract is genetically related as the majority of them were derived from marine organic matters sources (mainly algae) deposited under reducing environment and take the direction of increasing maturity and far away from the direction of biodegradation. Therefore, Masajid Formation is considered as effective source rocks for generating hydrocarbons, while Khatatba and Ras Qattara formations are the main source rocks for hydrocarbon accumulations in the Salam-3x well.